An appraisal of laboratory models of androgenetic alopecia: A systematic review - S. Ntshingila; N. P. Khumalo; M. Engel; A. T. Arowolo (Wiley, 2021)
Abstract Background Androgenetic alopecia (AGA) is the most common form of non‐scarring alopecia in humans. Several studies have used different laboratory models to study the pathogenesis and interventions for AGA. These study models have proved beneficial and have led to the approval of two drugs. However, the need to build on existing knowledge remains by examining the relevance of study models to the disease. Objective We sought to appraise laboratory or pre‐clinical models of AGA. Method We searched through databases (PubMed, ScienceDirect, Web of Science, World CAT, Scopus and Google Scholar) for articles on AGA‐related studies from 1942 to March 2019 with a focus on study models. Results The search rendered 101 studies after screening and deduplication. Several studies (70) used in vitro models, mostly consisting of two‐dimensional monolayer cells for experiments involving the characterization of androgen and 5‐alpha reductase (5AR) and inhibition thereof, the effects of dihydrotestosterone (DHT) and biomarker(s) of AGA. Twenty‐seven studies used in vivo models of mice and monkeys to investigate DHT synthesis, the expression and inhibition of 5AR and hair growth. Only four studies used AGA‐related or healthy excisional/punch biopsy explants as ex vivo models to study the action of 5AR inhibitors and AGA‐associated genes. No study used three‐dimensional [3‐D] organoids or organotypic human skin culture models. Conclusion We recommend clinically relevant laboratory models like human or patient‐derived 3‐D organoids or organotypic skin in AGA‐related studies. These models are closer to human scalp tissue and minimize the use of laboratory animals and could ultimately facilitate novel therapeutics.